Developmental and metabolic regulation of the Drosophila melanogaster 3-hydroxy-3-methylglutaryl coenzyme A reductase. - Gertler, F B (1988)
The enzyme 3-hydroxy-3-methylglutaryl coenzyme A (HMG CoA) reductase in Drosophila melanogaster synthesizes mevalonate for the production of nonsterol isoprenoids, which are essential for growth and differentiation. To understand the regulation and developmental role of HMG CoA reductase, we cloned the D. melanogaster HMG CoA reductase gene. The nucleotide sequence of the Drosophila HMG CoA reductase was determined from genomic and cDNA clones. A 2,748-base-pair open reading frame encoded a polypeptide of 916 amino acids (Mr, 98,165) that was similar to the hamster HMG CoA reductase. The C-terminal region had 56% identical residues and the N-terminal region had 7 potential transmembrane domains with 32 to 60% identical residues. In hamster HMG CoA reductase, the membrane regions were essential for posttranslational regulation. Since the Drosophila enzyme is not regulated by sterols, the strong N-terminal similarity was surprising. Two HMG CoA reductase mRNA transcripts, approximately 3.2 and 4 kilobases, were differentially expressed throughout Drosophila development. Mevalonate-fed Schneider cells showed a parallel reduction of both enzyme activity and abundance of the 4-kilobase mRNA transcript.